Considered Interests in the Decision to Dismiss an Incompetent Employee - Omair Sahi, Assist. Lect. Elham; Fathi Abdul Jalil, Researcher. Wad (Basra studies journal, 2024)
This study, titled "Considered Interests in the Decision to Dismiss an Incompetent Employee," aims to clarify the concept of an incompetent employee and discuss all the legal aspects related to organizing their legal status in light of Iraqi legislation. It also seeks to outline the scope and limits of the interests considered in issuing a decision to dismiss an incompetent employee.